Classical Guidance in Handling Cases of Sexual Violence in Elementary School Students - Rosita, Tita; Juntika Nurihsan; Dita Padiani Rahma (PrimaryEdu : Journal of Primary Education, 2024)
Schools are learning centers where students seek knowledge, and they must be safe, friendly environments free from violence. This research aims to improve the handling of sexual violence cases among elementary school students. The subjects were 420 students from grades 4 to 6 at SDN 106 Ajitunggal Cijambe Bandung, using a quasi-experimental method. Before receiving classical guidance services, students lacked awareness of the types of sexual violence, did not know whom to report to, and were afraid to inform teachers if they witnessed a friend experiencing sexual violence. However, after receiving classical guidance, (1) students became more aware of the dangers of promiscuity and sexually violent behaviors linked to social media, especially on platforms like TikTok, allowing them to discern appropriate content, (2) students became more open to seeking help from friends, teachers, and parents if they encountered sexual violence, and (3) students developed greater awareness and caution regarding new environments that might lead to sexual violence. This study concludes that classical guidance services are effective in increasing elementary students’ understanding and ability to handle sexual violence cases.